Metafora Konseptual dan Fungsi Skema Citra pada Mahfudzat Bertema Etika - Hanifa, Humaira Qisthi; Tajudin, Nur (Linguistik, Terjemahan, Sastra (LINGTERSA), 2026)
This study analyzes how ethical values in ten classical Arabic Mahfudzat are conceptualized through cognitive linguistic structures, particularly Conceptual Metaphor Theory and image schemas. Although Mahfudzat are known as concise moral aphorisms, this research shows that their ethical messages are systematically shaped through metaphorical mappings that reflect the cognitive framework of Arab culture. Using a qualitative descriptive method, the study examines ten Mahfudzat from the first and second levels of the Gontor curriculum to identify their source target domains, metaphor types, and underlying image schemas. The findings reveal a total of 10 metaphorical expressions consisting of 3 structural metaphors, 2 orientational metaphors, and 5 ontological metaphors, each supported by specific image schemas. Image schema analysis shows that spatial schemas (space) dominate the dataset, particularly the center periphery and up down patterns found in most entries, while the remaining data reveal scale and existence schemas. These results demonstrate that Mahfudzat encode ethical instruction not only linguistically but also cognitively, offering valuable insights for Arabic language pedagogy and future interdisciplinary research on morality and cognition.